Peningkatan Hasil Belajar Matematika Siswa Melalui Pembelajaran Berbantuan GeoGebra di Kelas XII IPA 9 SMA Negeri 1 Palembang - Ayu Mentari; Yanna Sanova (Universitas Maritim Raja Ali Haji, 2019)
The purpose of this classroom action research is to improve mathematics learning outcomes of students in XII Science 9 Senior High School Number 1 through GeoGebra assisted learning. Subject of this research are 29 students. The lesson taught in this study are maximum and minimum value, monotonicity, slope, and concavity of trigonometric function. First cycle was held in 3 meetings and the second cycle held in 2 meetings. Instrument used is a test of learning outcomes and observation. Learning outcomes test is used to find out student’s achievement in each cycle and observation used to collect data during learning process. The data are analized quantitatively and descriptively. Results of the study indicate that the average score of XII Science 9 in the first cycle is 50,00 and in the second cycle is 82,76. The result of this study show that GeoGebra assisted learning can improve mathematics learning outcomes which is equal to 80% students have achieved completeness in second cycle